SINTESIS DAN UJI BIOAKTIVITAS SENYAWA ANALOG UK-3A 6-HIDROKSI-N-OKTILNIKOTINAMIDA - Dadan Ridwanuloh; Herry Cahyana; Muhammad Hanafi (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2016)
abstrak